Estudo, análise e projeto de sistemas magnéticos aplicados a conversores estáticos - Bolsi, Pedro Cerutti (2020)
Given that the volumetric design of transformers and inductors is directly connected to losses, the correct prediction of these is fundamental for their optimization. With this vision, this work presents techniques for the modeling of copper and core losses on magnetic devices, through the discussion of two subjects relevant to magnetic design. The first one is a study on core loss modeling, making use of empirical models based on Steinmetz’s equation. A comparative analysis among the main analytical models is done, as well as an experimental evaluation, in order to verify the precision of these models, and the influence of the operating point on losses, including premagnetization. For the evaluated material, of High Flux technology, it is shown that, for the evaluated range, premagnetization does not have an influence on core loss. The model recommended by the manufacturer, based on Steinmetz’s equation, is valid for 0,5 duty cycle, and the IGSE (Improved Generalized Steinmetz Equation), which does account for variations of duty cycle, has good accuracy. The second subject discussed is the re-designing of the transformer of a Line Interactive UPS aiming to improve its global efficiency. By modeling transformer losses, the characterization, quantification and relativization of loss allows for the identification of points of improvement in the transformer design, and with the reproduction of the LI-UPS via simulation, the efficiency of new transformer prototypes is estimated with the experimentally co-validated loss models. Making small changes on the transformer design, the analyzed prototypes raised global efficiency by up to 1,11% at the highest point of the original efficiency curve, and up to 2,60% in higher power levels.